Outcome of Management of Pediatric Subtrochanteric Femoral Fracture with Broad Dynamic Compression Plate and Proximal Cancellous Screw through the Femoral Neck - Karki, Prateek; Shrestha, Dinesh Kumar; Ranabhat, Roshani (Journal of Nepalgunj Medical College, 2021)
Introduction: Pediatric subtrochanteric femoral fracture can be managed with traction followed by spica, intramedullary elastic nailing, plating or external fixators. The prognosis largely depends on adequate reduction and stable fixation. Aims:The aim of this study was to evaluate functional outcome of pediatric subtrochanteric femoral fracture treated with broad dynamic compression plate. Methods: This prospective observational study consisted of 32 children between the age 7 to 15 years, with an average of 10.06 years ± 2.29, with subtrochanteric femoral fracture. Fractures were reduced by an open reduction through lateral approach and stabilized with a broad dynamic compression plate along with a proximal cancellous screw through the femoral neck. All patients were followed for 15 months and the results were evaluated on the basis of Flynn scoring system. Results: All fractures united with a mean duration of 12.6 weeks ± 0.91. Average hospital stay was 8.43 days (5 to 14 days). Functional outcome was excellent in 84.38% (27 patients) and satisfactory in 15.62% (5 patients). Full weight bearing was started after mean duration of 16.62 weeks ± 0.91. Implants were removed at an average of 11.21 months ± 1.06. There were no significant limb length discrepancies, deep infections, re-fracture, osteomyelitis and avascular necrosis. Conclusion: This prospective study showed good functional outcome in pediatric patients having subtrochanteric femoral fractures who were treated with a broad dynamic compression plate and a proximal cancellous screw through neck.